Organizational Culture in the OAP Welfare Program in Biak Numfor District - Rudiyansyah Rudiyansyah (Journal Social Civilecial, 2025)
This study aims to analyze the organizational culture in the implementation of the Indigenous Papuan (OAP) welfare program in Biak Numfor Regency, with an emphasis on support for innovation, tolerance for risk and failure, and appreciation for innovative behavior. This study uses a qualitative method with a phenomenological approach. Data were obtained through in-depth interviews, field observations, and documentation, then analyzed interpretively to understand the values, bureaucratic practices, institutional relations, and implementation patterns of the Indigenous Papuan welfare program at the regional level. The results of the study indicate that the organizational culture in the Indigenous Papuan welfare program has a hierarchical-communal character with developing adaptive capacity. Support for innovation is evident through a variety of programs, such as decent housing, basic food assistance, direct cash assistance (BLT), boat engines, and business assistance. Tolerance for risk and failure is evident through the recipient selection mechanism, self-management system, and technical supervision, although it is still more oriented towards administrative control than institutional learning. Appreciation for innovative behavior is evident through community involvement, the role of village governments, and the social legitimacy of beneficiaries, but has not been fully institutionalized in the formal organizational system. The organizational culture within the Indigenous Peoples' (OPP) welfare program in Biak Numfor Regency has provided a foundation for responsive, accountable, and community-accepted program implementation. However, this culture still needs to be strengthened through institutionalization of innovation, risk-based learning, inter-program integration, and recognition of innovative practices to foster broader, deeper, and more sustainable transformation of Indigenous Peoples' (OPP) welfare.